2010
DOI: 10.1111/j.1745-4514.2009.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Antiacetylcholinesterase Activities of the Extracts of Pistacia Atlantica Desf. Leaves

Abstract: Pistacia atlantica Desf. (Anacardiaceae), a tree that is widely distributed in the Marmara, Mediterranean and Central Anatolia regions of Turkey, has been utilized traditionally for culinary and medicinal purposes. In the present study, methanolic and ethyl acetate extracts were prepared from young leaves of P. atlantica Desf., which were collected during the spring, and their antioxidant, scavenging, chelating and anti‐acetylcholinesterase activities were evaluated. Both of the extracts showed strong antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 41 publications
4
35
2
Order By: Relevance
“…As shown in Table 4, DPPH radicals scavenging activities respectively reached 53%, 63%, 70%, and 73% in samples sonicated for 0, 20, 40, and 60 min. The experimental result showed that the scavenging activities of blueberry juice on DPPH The superoxide could combine with other radicals, such as hydroxyl and nitric oxide, to form stronger reactive species and possess greater oxidative ability (Peksel et al, 2010). Table 4 exhibited that scavenging activities of superoxide radicals increased from 41% up to 48%, 56%, and 62% in blueberry juice sonicated for 0, 20, 40, and 60 min, respectively.…”
Section: Impact Of Sonication On Radical Scavenging Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Table 4, DPPH radicals scavenging activities respectively reached 53%, 63%, 70%, and 73% in samples sonicated for 0, 20, 40, and 60 min. The experimental result showed that the scavenging activities of blueberry juice on DPPH The superoxide could combine with other radicals, such as hydroxyl and nitric oxide, to form stronger reactive species and possess greater oxidative ability (Peksel et al, 2010). Table 4 exhibited that scavenging activities of superoxide radicals increased from 41% up to 48%, 56%, and 62% in blueberry juice sonicated for 0, 20, 40, and 60 min, respectively.…”
Section: Impact Of Sonication On Radical Scavenging Activitymentioning
confidence: 96%
“…Radicals scavenging activities in food were very important to stay the health of consumers because free radicals could accelerate lipids oxidation and induce serious tissue damage (Peksel et al, 2010). Determination of DPPH radical was simple and effective method to assess antioxidant ability of the food.…”
Section: Impact Of Sonication On Radical Scavenging Activitymentioning
confidence: 99%
“…Although superoxide was a relatively weak oxidant, its combination with other reactive species, such as nitric oxide and hydroxyl, might yield stronger reactive species which possessed greater oxidative ability than the precursor to initiate lipids peroxidation 14,15 . Furthermore, superoxide is also known to indirectly induce lipid peroxidation as a result of H 2 O 2 formation, creating precursors of hydroxyl radicals 13 .…”
Section: Superoxide Radical Scavenging Activitymentioning
confidence: 99%
“…Excessive formation of free radicals accelerated the oxidation of lipids in foods and induced severe damage to adjacent biomolecules. [29,30] DPPH assay evaluated the radical scavenging ability of antioxidants. Under ethanol solution, antioxidants could interact with the DPPH radical and transfer an electron or hydrogen atom to the DPPH radical, thus neutralizing its free radical character.…”
Section: Antioxidant Activities Of Aadf Melanin and Aafb Melaninmentioning
confidence: 99%
“…Although the superoxide was a relatively weak oxidant, its combination with other reactive species, such as nitric oxide and hydroxyl, might yield stronger reactive species, which possessed greater oxidative ability than the precursor to initiate lipids peroxidation in a longer time. [29,32] In addition, superoxide was also known to indirectly induce lipid peroxidation as a result of H 2 O 2 formation, creating precursors of hydroxyl radical. [28] Hydrogen-donating ability was a primary index of antioxidants.…”
Section: Antioxidant Activities Of Aadf Melanin and Aafb Melaninmentioning
confidence: 99%